2020
DOI: 10.1021/acs.iecr.0c03915
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Additives on the Structure and Hydrotreating Activity of a CoMoS/Multiwalled Carbon Nanotube Catalyst

Abstract: A comparative study of the effect of citric acid (CA), nitrilotriacetic acid (NTA), and diethylene glycol (DEG) used for the preparation of impregnation solution on the properties and catalytic performance of CoMoS/multiwalled carbon nanotube (MWCNT) hydrotreating catalyst was carried out. For a deeper understanding of the role of organic additives during CoMoS catalyst preparation, thermal analysis, nitrogen physisorption, X-ray photoelectron spectroscopy, and high-resolution transmission electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…CoMo/Al 2 O 3 and CoMo/C@Al 2 O 3 - x catalysts were synthesized by impregnating the corresponding supports with aqueous solutions of ammonium heptamolybdate tetrahydrate (Sigma-Aldrich), cobalt­(II) carbonate hydrate (Sigma-Aldrich), and citric acid (Reachim Ltd.) as organic complexing agent. The preparation procedure is described in more detail in. , Impregnation solutions were prepared in such a way as to provide 3.2 and 12.0 wt % of Co and Mo in the catalysts, respectively. The prepared catalyst samples were dried for 4 h at 120 °C in a drying chamber with forced convection (air change rate of 80 x/h).…”
Section: Methodsmentioning
confidence: 99%
“…CoMo/Al 2 O 3 and CoMo/C@Al 2 O 3 - x catalysts were synthesized by impregnating the corresponding supports with aqueous solutions of ammonium heptamolybdate tetrahydrate (Sigma-Aldrich), cobalt­(II) carbonate hydrate (Sigma-Aldrich), and citric acid (Reachim Ltd.) as organic complexing agent. The preparation procedure is described in more detail in. , Impregnation solutions were prepared in such a way as to provide 3.2 and 12.0 wt % of Co and Mo in the catalysts, respectively. The prepared catalyst samples were dried for 4 h at 120 °C in a drying chamber with forced convection (air change rate of 80 x/h).…”
Section: Methodsmentioning
confidence: 99%
“…Comparative studies (Vatutina et al, 2020) using CoMo formulations over multi-walled carbon nanotubes (MWCNT) found that chelating citric acid was more efficient than diethylene glycol addition in improving DBT HDS and quinoline hydrodenitrogenation. Decreased support-Mo interaction provoked by the later additive was not very effective in promoting activity as impregnated phases were not strongly bonded to MWCNT.…”
Section: Introductionmentioning
confidence: 99%